FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMSI FUNCTIONAL FOOD DI SURABAYA - Evi Thelia Sari (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2014)
This article has a purpose to analyse the factors that influence functional food consumption in Surabaya. Based on the data process of 100 respondents using confirmatory factory analysis, there are two factors found,  factor1 is  46,649% named as Product awareness  and Factor 2 named as Product knowledge 19,149%. Total varians 65,798%  less than100 % means that there is another factor unexposed here. The dominant factor is product awareness consists of  availability, value and reference variables and the second factor, product knowledge consists of  necessity, safety and reward variables is not the dominant factor since the respondents do not really understand the detail function of each food consumed, but they believe the functional food is good for them based on their references. Another unexposed factor could be intensive advertising, publicity, government intervention program in enhancing society health and so on.